Perceptions of Substance Use Disorder and Associated Sanctions: A Factorial Vignette Experiment - Kuettel, Benjamin T. (Criminal justice review, 2023)
This study examines whether characteristics of people who use drugs (PWUD) influence public perceptions of substance use disorder (SUD) and punitiveness. Using a full-factorial vignette experiment, a nationwide sample (N = 448), and a series of regression models, I estimate the causal effect of characteristics of PWUD on substance use evaluations and punitiveness. Results reveal that drug type and prior criminal drug record affected both SUD and punitive judgements, implying a prosocial punitiveness, where punishments are intended to rehabilitate. Demographics of PWUD (e.g., race, sex, etc.) mattered little. However, racial resentment moderated the relationship between SUD and punitiveness, suggesting aggressive punitiveness. These findings imply that SUD evaluations and punitiveness are linked in the public mind, suggesting that citizens may see punishments as a way to address SUD by helping PWUD recover. This is not true for racially resentful respondents, who appear to want to punish PWUD for punishment's sake.